2007
DOI: 10.1021/cm0715242
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio Study of Lithium Diffusion in Titanium Disulfide Nanotubes

Abstract: Using density functional theory (DFT), we have investigated the mobility and insertion potential of Li on single-walled TiS2 nanotubes as a function of radius. To explore large radii, the nanotube surface is modeled as a curved surface. For small tubes, for which DFT calculations are practical on the complete tube, we find that strain energies, voltages, and activation barriers calculated with the curved surface method are nearly the same as those calculated with a full nanotube. Our results show that, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 65 publications
3
44
0
Order By: Relevance
“…19,20 The linear interpolation was applied between the initial and nal states of the ion diffusion path with nine and eight intermediate images for hexagonal (H) monolayer and trigonal (T) bulk VS 2 , respectively. 19,20 The linear interpolation was applied between the initial and nal states of the ion diffusion path with nine and eight intermediate images for hexagonal (H) monolayer and trigonal (T) bulk VS 2 , respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…19,20 The linear interpolation was applied between the initial and nal states of the ion diffusion path with nine and eight intermediate images for hexagonal (H) monolayer and trigonal (T) bulk VS 2 , respectively. 19,20 The linear interpolation was applied between the initial and nal states of the ion diffusion path with nine and eight intermediate images for hexagonal (H) monolayer and trigonal (T) bulk VS 2 , respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[28][29][30][31][32]63 Bulk TiS 2 has long been studied as an intercalation compound and TiS 2 nanotubes have shown the ability to store hydrogen and lithium. Bulk TiS 2 forms the CdI 2 -1T structure which consists of layers of Ti atoms octahedrally coordinated by S atoms.…”
Section: B Tis 2 Structurementioning
confidence: 99%
“…Bulk TiS 2 forms the CdI 2 -1T structure which consists of layers of Ti atoms octahedrally coordinated by S atoms. 63,65,66 These triple layers ͑S-Ti-S͒ are separated by a Van der Waals gap and stacked such that the titanium atoms project on top of each other. This triple layer is the basic structural unit of TiS 2 layered nanotubes.…”
Section: B Tis 2 Structurementioning
confidence: 99%
“…Therefore, in recent years, the cation diffusion in h-Li x TiS 2 has been the topic of numerous investigations, both experimentally [9][10][11][12][13] and theoretically [14][15][16][17]. By 7 Li solid state NMR investigation, Prigge et al [9] have observed a fast Li + mobility in h-Li x TiS 2 with measured activation energies of 0.25 eV and 0.20 eV for x = 0.75 and 1.0, respectively.…”
Section: Introductionmentioning
confidence: 99%